Genomic Modeling of an Outbreak of Multidrug-Resistant Shigella sonnei, California, USA, 2023–2024 - Tyler Lloyd; Sana M. Khan; Dustin Heaton; Munira Shemsu; Vici Varghese; Jay Graham; Misha Gregory; Penny Dorfman; Megan Talton; Jessica DeVol; Nicola F. Müller; Kavita K. Trivedi (Emerging Infectious Diseases)
We report the detection of a Shigella sonnei outbreak from a small investigation in the San Francisco Bay area, California, USA, in 2024. By combining outbreak investigation with genomic sequencing, we show the utility of phylodynamics to aid outbreak investigations of bacterial pathogens by state or local public health departments.